Eksplorasi Kerajinan Anyaman Bambu Desa Loyok: Potensi, Tantangan, dan Dampak Pelestarian Warisan Budaya - Ulan Safitri; Abdul Hafiz; Muhammad Shulhan Hadi (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
Bamboo weaving in Loyok Village is a cultural heritage practice that integrates inherited craftsmanship, local resource use, and community livelihoods. This study aims to identify its potential, analyze preservation challenges, and explain the impacts of ongoing conservation efforts in Loyok Village, Sikur District, East Lombok Regency. A qualitative descriptive approach was employed from July to September 2025. Data were collected through observation, structured and unstructured interviews, and documentation involving 13 informants, including artisans, art-shop owners, guides, local administrative heads, and village staff. Data were analyzed interactively through collection, reduction, display, and conclusion drawing and verification, while prolonged observation and triangulation were used to strengthen credibility. The findings reveal three major areas of potential: the availability of bamboo and surrounding raw-material supplies, intergenerational weaving skills, and opportunities for product development, digital markets, and educational tourism. Preservation is constrained by competition from inexpensive and practical modern products, declining interest among younger people, and limited local consumer appreciation of the value of manual craftsmanship. Conservation efforts generate economic benefits through household income and employment, while reinforcing local identity, cultural awareness, and the use of relatively environmentally friendly materials. Sustainable preservation therefore requires apprenticeship-based regeneration, design innovation that maintains authenticity, stronger digital marketing, experiential cultural tourism, and coordinated collaboration among village government, artisans, educational institutions, and tourism actors.